PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN ASIMETRI INFORMASI SEBAGAI VARIABEL INTERVENING (Studi Empiris pada SKPD se-Eks Karesidenan Kedu) - Elma Octavia Pradita; Haryanto Haryanto (Diponegoro Journal of Accounting, 2017)
This study aims to examine the relationship between budgetary participation and budgetary slack in a public sector organization. It also attempts to examine whether information asymmetry mediates the relationship between budgetary participation and budgetary slack.This study uses primary data obtained from questionnaires distributed to budget planner in a public sector organization. This study used a sample of 75 respondents using purposive sampling. A path analysis was utilize to examine the direct and indirect effects of budgetary participation on budgetary slack. .The analysis results indicate that 1) Budgetary participation has no relationship with budgetary slack. 2) Budgetary participation and information asymmetry have a positive relationship. 3) Information asymmetry and budgetary slack have a positive relationship. 4) Budgetary participation did not indirectly affect budgetary slack through information asymmetry as an intervening variable.